2018
DOI: 10.1200/cci.17.00149
|View full text |Cite
|
Sign up to set email alerts
|

The HOPE Pilot Study: Harnessing Patient-Reported Outcomes and Biometric Data to Enhance Cancer Care

Abstract: Purpose: Integrating patient-reported outcomes (PROs) into clinical practice is an increasingly promising strategy for improving patients’ symptoms, communication, and clinical outcomes. The objective of this study was to assess the feasibility, acceptability, and perceived effectiveness of a mobile health intervention designed to collect PROs and activity data as a measure of health status. Patients and Methods: Pilot intervention with 10 patients with gynecologic cancers receiving palliative chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 36 publications
1
81
0
Order By: Relevance
“…Older cancer survivors may benefit from newer technology (i.e., internet, social media, wearables) for cancer care [21]. In addition to the potential informational benefits, remote symptom monitoring, online support groups, and selfmanagement applications may all help to improve both the quality of life and care for cancer survivors, especially older cancer survivors who may not be able to easily attend as many appointments or visits [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Older cancer survivors may benefit from newer technology (i.e., internet, social media, wearables) for cancer care [21]. In addition to the potential informational benefits, remote symptom monitoring, online support groups, and selfmanagement applications may all help to improve both the quality of life and care for cancer survivors, especially older cancer survivors who may not be able to easily attend as many appointments or visits [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…However, no details on usability aspects and acceptance were given. Wright et al [24] evaluated an accelerometer-based monitoring system over a period of 30 days in 10 gynecological patients undergoing palliative chemotherapy focusing on feasibility, acceptability, and perceived effectiveness. These patients used a smartphone with the Beiwe research platform (also a tool for the collection of data) on it and two accelerometers.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of seven breast cancer patients in active treatment, more time at home or at locations of friends and family members was associated with better mood and less anxiety and depression while more time spent at hospitals and clinics was associated with worse mood 45 . In a sample of 10 gynecologic cancer patients, Fitbit and smartphone sensor data were actively monitored for anomalies; this led the research team to identify a patient with severe nausea and vomiting whose symptoms were then able to be managed over the phone as well as a patient who took fewer steps and spent less time away from home prior to an emergency department visit 46 . Finally, a recent study collected both smartphone and wearable sensor data as well as patient-reported pain and distress ratings and quality of life measures in 25 palliative cancer patients 47 .…”
Section: Smartphone Sensors In Oncology Researchmentioning
confidence: 99%
“…We identified 14 prospective studies since 2016 that have examined a variety of oncology populations before, during, and after cancer treatment and have included a range of consumer wearable devices and smartphone sensing frameworks (see Table 1 ). Most studies have included very small samples (median n = 34.5, range 7–71), and only a handful have used real-time sensor data to inform clinical care 42 , 46 . Larger-scale longitudinal studies that implement mobile sensing in clinical settings are needed.…”
Section: Summary Of Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation